The bond and money markets strategy, trading, analysis - Choudhry, Moorad
The Bond and Money Markets: Strategy, Trading, Analysis explains and analyses all aspects of the bond and money markets and is both an introduction for newcomers and an advanced text for experienced market practitioners and graduate students. Those with experience of the industry at all levels will find the book invaluable as a standard reference work. The book features coverage of:* Government and Corporate bonds, Eurobonds, callable bonds, convertibles* Asset-backed bonds including mortgages and CDOs* Derivative instruments including bond futures, swaps, options, structured products, and opti.